Giving Hope to Refugee Families: Carry the Future. Issue 6 (November 2017) - Callister, Lynn Clark
Abstract : Carry the Future is a grassroots movement to help refuges families which operates without major overhead or marketing costs so it is effective and efficient. Our global health expert, Dr. Lynn Callister, tells us how the organization helps mothers and babies and what you can do to get involved.